Reconstruction of sedimentary environments in the Djadokhta Formation, Udyn Sayr, Gobi desert, Mongolia - Saneyoshi, Mototaka; Asai, Hitomi; Mainbayar, Buuvei; Tanabe, Tomohiro; Ishigaki, Shinobu; Tsogtbaatar, Khishigjav (Mongolian Journal of Paleontology, 2021)
The Djadokhta Formation in Udyn Sayr in the southwestern part of the Gobi desert, Mongolia, is described based on sedimentary facies. The succession is composed of eolian and fluvial facies, with interfingering stratigraphic intervals. The fluvial association is indicated by the presence of caliche, suggesting seasonally wet and dry conditions. The eolian deposits contain the most fossils of vertebrates such as Protoceratopsidae, reptiles and Mesozoic mammals, which form a rich part of the succession in the fossil locality. This suggests that eolian environments were the main habitat for vertebrates during the sedimentation period.